IMPLEMENTASI NILAI PENDIDIKAN KARAKTER RELIGIUS, TOLERANSI, KEJUJURAN, DAN DISIPLIN DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Abdul Hakim; Seni Dwi Febrianty (Institut Pendidikan Indonesia, 2022)
Character education in thematic learning is still experiencing many problems. The purpose of this study is to describe:1) Implementation of the four values of character education in the thematic learning process; 2) Obstacles encountered in the process of implementing the four values of character education in thematic learning; 3) Solutions in dealing with problems in the process of implementing the four values of character education in thematic learning. Character values that are focused on by researchers are religious character values, tolerance character values, honest character values, and discipline character values. This study uses a qualitative phenomenological approach with descriptive type. The subjects of this study were teachers and third grade students. Teachers develop character education in the learning process by applying habits. The obstacles faced are in inadequate facilities and infrastructure such as learning media, attitude assessment and family factors. Efforts are being made to develop media and learning methods and conduct attitude assessments flexibly according to thefindings in the field.